Literature Review: The Support Needs of The Nurse Mentors in Their Mentoring Role - Sisinyana Hannah Khunou; Kholofelo Lorraine Matlhaba (Journal of Ners and Midwifery, 2023)
In order to develop effective mentoring programme, it is important to identify the needs of the nurse mentors.Â  A lot has been documented about the needs of the nurse mentees, however, there is a dearth of recent literature finding the support needs of the nurse mentors. The aim of this integrative review was to synthesize the literature on the support needs of the nurse mentors in their mentoring role. The search was steered across Cumulative Index to Nursing and Allied Health Literature; Direct of Open Access Journals; Google Scholar, PubMed/MEDLINE, Science Direct, and SCOPUS, in order to identify challenges and support that need to provide to the nurse mentors in their mentoring role. The Medical Subject Headings according to National Library of Medicine was used to search for the key concepts. Key search concepts were entered into the query box on the main PubMed page and searched. The search details page was check to determine how PubMed processed the search. The same concepts were used on the database to search for the articles which were included in this review. Seven subthemes, twenty categories were identified and classified into two main themes: Challenges to effective mentoring; Support needed by the nurse mentors. The review identifies challenges faced by nurse mentors and concludes that they need support. This study suggests that policy makers should make a concerted effort by availing resources for mentoring role. Workshops to equip mentors and collaboration between different stakeholders might help to enhance the support of the nurse mentors. Future research should analyse collaboration in support of the nurse mentors in their mentoring role